Public Service Registration Land In City Pekanbaru - Sufian Hamim; Detri Karya; Fabellany Sovina; Syarifah Ermayuna (International Conference On Law And Social Sciences, 2024)
Increasing amount resident in a way No direct result need will land the more increase. Besides The increasing need for development, there is also a need for housing and a need for land for interest other. Moment This is the amount land Which available starting felt very limited , deep meaning No increase. This research is qualitative in nature, and the type of research is descriptive, namely research that describes or explain in a way clear And detailed about Service Public Registration Land in Pekanbaru City . Design study related tightly with research methods; it could even be said that the two cannot be separated from each other by design study made with research methods Which chosen. Land registration No only protects the owner but also determines the status of a plot of land: who owns it, what rights they have, how much breadth, used For What, And etc (Dalimunthe 2000, 132). Guarantee certainty law Which will realized in land registration, this includes locking the status of registered rights, trusting the subject of the rights, and certainty of the object right registration this land produces certificate that proves it They are right.